Deliberative Democracy Formation In Political Education: A Case Study On The National Democratic Party (Nasdem) Of DKI Jakarta - Muhammad Shabri Sambojo Utomo; Mochamad Iqbal Jatmiko (Eduvest - Journal of Universal Studies, 2024)
This study aims to analyze the formation of deliberative democracy in political education within the National Democratic Party (NasDem) of DKI Jakarta. By employing the concept of deliberative democracy, we argue that the NasDem Party of DKI Jakarta applies a democratic intersubjective dialogue process in decision-making regarding internal party political education. Although research on political education in general within political parties in Indonesia has been widely discussed, this paper complements previous studies by considering democratic inter-agent interactions and analyzing the discourse of deliberative democracy in political education within the NasDem Party of DKI Jakarta. Through qualitative exploration with descriptive case studies of two informants, field findings indicate that interactions in political education within the NasDem Party of DKI Jakarta are democratic in line with the party's ideological foundation, which guarantees internal democracy and promotes public democratization. Additionally, political parties also engage in empowering active members through participatory procedures and facilitate deliberative decisions in legitimizing internal political education from the village level to the provincial level. These findings contribute to an intra-party deliberative democracy model aimed at empowering members and offering a political public forum that prioritizes deliberation in influencing decisions.